Vitamin D supplementation does not improve CVD risk factors in vitamin D-insufficient subjects. Issue 6 (June 2018) - Kubiak, Julia; Thorsby, Per Medbøe; Kamycheva, Elena; Jorde, Rolf
Abstract : Objective: Low serum 25(OH)D levels are associated with cardiovascular disease (CVD) and some of its risk factors. However, in interventional studies, the effects of vitamin D supplementation have been uncertain, possibly due to inclusion of vitamin D-sufficient subjects. Our aim was therefore to examine effects of vitamin D supplementation on CVD risk factors in vitamin D-insufficient subjects. Design: Double-blinded randomized controlled trial. Methods: A 4-month interventional study with high-dose vitamin D (100, 000 IU loading dose, followed by 20, 000 IU/week) or placebo with measurements of blood pressure, lipids (total-, LDL- and HDL-cholesterol, triglycerides, apolipoproteins A1 and B), and glucose metabolism parameters (blood glucose, HbA1c, serum human receptors for advanced glycation end products (sRAGE), insulin, C-peptide and HOMA-IR). Results: A total of 422 subjects with mean serum 25(OH)D level 34 nmol/L were included, with 411 subjects completing the study. Serum 25(OH)D levels increased with 56 nmol/L and decreased with 4 nmol/L in the vitamin D and placebo group, respectively. We found no statistically significant differences between the two groups in any of the measured CVD risk factors, except for a minor increase in sRAGE in the vitamin D group. Stratified analyses of subjects with low baseline serum 25(OH)D levels alone, or combined with blood pressure, lipid and HOMA-IR values above the median for the cohort, did not skew the results in favour of vitamin D supplementation. Conclusion: Supplementation with vitamin D in subjects with baseline vitamin D insufficiency does not improve CVD risk factor profile.